2007
DOI: 10.1080/87565640701228732
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Evaluation of Human Brain Development

Abstract: The complex development of the human brain during infancy can only be understood by convergent structural, functional, and behavioral measurements. The evaluation of event-related potentials (ERPs) is the most effective current way to look at infant brain function. ERP paradigms can be used to examine the simple transmission of sensory information to the cortex and the discrimination of this information within the cortex. The main developmental changes involve localization of function as the brain becomes tune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 119 publications
5
68
0
2
Order By: Relevance
“…Latency changes across age have also been described (Allison et al, 1984;Zemon et al, 1995). Shorter P1 peak latency in adults than in children may reflect the increase in processing speed due to myelinisation (Picton and Taylor, 2007). Several studies have reported that P100 latency stabilizes around 20 years of age (Shaw and Cant, 1981;Allison et al, 1984;Emmerson-Hanover et al, 1994).…”
Section: P1-n1 Range: Pre-linguistic Processesmentioning
confidence: 87%
See 1 more Smart Citation
“…Latency changes across age have also been described (Allison et al, 1984;Zemon et al, 1995). Shorter P1 peak latency in adults than in children may reflect the increase in processing speed due to myelinisation (Picton and Taylor, 2007). Several studies have reported that P100 latency stabilizes around 20 years of age (Shaw and Cant, 1981;Allison et al, 1984;Emmerson-Hanover et al, 1994).…”
Section: P1-n1 Range: Pre-linguistic Processesmentioning
confidence: 87%
“…A decrease in the amplitudes of VEP with age has been repeatedly described using different kinds of visual stimuli (Allison et al, 1984;Brecelj et al, 2002;Hoffmann et al, 2001;Holcomb, Coffey and Neville, 1992;Mahajan and McArtur, 2012;Taylor et al, 2004). Larger amplitudes in children have been attributed to less thick skulls or to generators being closer to the surface electrode in smaller brains (Chauveau et al, 2004;Picton and Taylor, 2007). Alternatively, amplitude decreases may result from increasing automaticity; the same processes require fewer resources, leading to a decrease in cerebral activation, a phenomenon that has been described in many developmental brain imaging studies (Durston and Casey, 2006).…”
Section: P1-n1 Range: Pre-linguistic Processesmentioning
confidence: 99%
“…It is known that TNF alpha affects oligodendrocytes that in course can effect myelination (e.g., Huang et al 2002), which could lead to differences in ERP latencies and response times. In fact, ERPs have been used as a measure to infer the status of myelination (Lippe et al 2007;Picton and Taylor 2007).…”
Section: Attentional Processing and Action Selectionmentioning
confidence: 99%
“…While numerous developmental studies have used electrophysiological techniques (namely, EEG and event-related potentials; for reviews, see [1,38,43]), structural MRI (for reviews, see [29,42]), and functional MRI (for examples, see [15,50]), the use of MEG offers the unprecedented opportunity to apply its exquisite spatio-temporal resolution to examining the complexities and intricacies of typical development and, as a consequence, atypical development. The availability of whole head MEG systems, with more than 300 recording sensors, attests to the maturity of MEG instrumentation.…”
Section: Introductionmentioning
confidence: 99%